Environmental Management System Implementation in MSMEs: A Literature Review - Michelle Gunawan; Riri Asyahira; Filson M Sidjabat (Jurnal Serambi Engineering, 2020)
The amount of MSMEs units about 99.99 percent of the overall number of business operators in Indonesia showed that MSMEs play a significant role in economic growth and development. At the same time, MSMEs cumulative contribution to environmental issues is not recorded MSMEs participation in the cleaner environment has not yet been noticed. Thus, the environmental management system for MSMes is crucial. This study is a literature review about the implementation of the ISO 14001 environmental management system in MSMEs, challenges and its future potential. The result and discussion discussed the case study of ISO 14001 implementation in Indonesia and other countries. Case studies from Indonesia and other countries showed that implementation of ISO 14001 is possible for MSMEs. The biggest challenges of its implementation is cost, the competence of employees, and resources available for the organization. An alternative for overcoming these challenges is implementing other models of EMS that is more suitable for MSMEs. The important aspects is the environmental awareness of the stakeholders and the internal and external drivers within the organization. Further studies can be done to research specific case studies of EMS such as ISO 14001 or AMEMs implementation in MSMEs.